Long-Term Trends of Adult Survival and Productivity in European Songbirds : Role of Migration Strategy and Temperature Gradient Within Species' Ranges - Nousiainen, Inari; Lehikoinen, Aleksi; Piha, Markus; Lehikoinen, Petteri; Robinson, Robert; Arizaga, Juan; Cepák, Jaroslav; Fiedler, Wolfgang; Geiter, Olaf; Henshaw, Ian; Herrmann, Christof; Illa, Marc; et al. (Wiley-Blackwell, 2026)
Aim: To understand species population ecology, we need to study how trends of demographic drivers change over time and space, especially so under current rapid climate change. However, knowledge on long-term trends of survival and productivity, especially using multiple species over large spatial scales, is scarce. Here, we examined the long-term trends of adult survival and productivity of European songbirds, their relation to temperature gradients within species' ranges, and different traits across multiple species over large spatial scales. Location: Ten countries in Europe. Time Period: 2001–2021. Major Taxa Studied: 28 songbird species. Methods: We used bird ringing data from the European Constant Effort Ringing scheme (CES), with 1.2 million captures of birds. We investigated the long-term trends of adult survival and productivity in relation to temperature gradients within species' ranges. We also tested differences in the long-term trends of demographic measures in relation to species' migratory strategies (long-distance migrants vs. short-distance migrants and residents) and long-term population trends. Results: There was no apparent major change in the long-term trends of either adult survival or productivity, and they did not show differences along the range gradient. Long-term trends of productivity differed between migratory strategies: long-distance migrants showed more negative trends in productivity than short-distance migrants and residents, while survival trends were similar between the two groups. Trends in both adult survival and productivity had equal positive connections with the population trends of songbirds.Main ConclusionsThe difference in long-term trends of productivity between migratory strategies highlights the importance of different conservation efforts for long-distance migrants compared to short-distance or resident birds.
Keywords: adult survival; demography; passerines; population ecology; productivity; species' ranges